Investigation of moisture effect on methane adsorption capacity of shale samples - Zou, Jie; Rezaee, M. Reza; Xie, Quan; You, L.; Liu, K.; Saeedi, Ali (Elsevier Ltd, 2018)
© 2018 Elsevier Ltd. The existing moisture in shale samples makes the evaluation for shale gas reservoirs more difficult due to its impact on the methane adsorption capacity and pore structure measurements. This paper compares the pore structure characteristics and methane adsorption capacity between dry and wet shale samples from Perth Basin, Western Australia. Pores with size between 0.4 nm and 100 nm were quantified by low-pressure N 2 and CO 2 adsorption. The comparative results demonstrate that moisture could alter the pore size distribution for big pores ( > 16 nm) and small pores (0.4–16 nm) in different ways. For each sample, the moisture effect on methane adsorption in shales changes with pressure: moisture effect on methane adsorption is more pronounced at lower pressure than higher pressure. For all samples, the effect of moisture on methane adsorption is related to the total organic carbon (TOC) content. Moisture could reduce methane adsorption by blocking clay- hosted small pores directly and organic matter-hosted small pores indirectly in high TOC samples. This phenomenon can effectively lead to a reduced Langmuir volume (V L ) and increased Langmuir pressure (P L ) when moisture exists.